Computational fluid dynamics : principles and applications - Blazek, J. (Elsevier, 2005)
Computational Fluid Dynamics (CFD) is an important design tool in engineering and also a substantial research tool in various physical sciences as well as in biology. The objective of this book is to provide university students with a solid foundation for understanding the numerical methods employed in todays CFD and to familiarise them with modern CFD codes by hands-on experience. It is also intended for engineers and scientists starting to work in the field of CFD or for those who apply CFD codes. Due to the detailed index, the text can serve as a reference handbook too. Each chapter includes an extensive bibliography, which provides an excellent basis for further studies. The accompanying CD-ROM contains the sources of 1-D and 2-D Euler and Navier-Stokes flow solvers (structured and unstructured) as well as of grid generators. Provided are also tools for Von Neumann stability analysis of 1-D model equations. Finally, the CD-ROM includes the source code of a dedicated visualisation software with graphical user interface.